Adaptation Strategies of Traditional Fishermen in Sutera Sub-District, Pesisir Selatan Regency on Climate Change - Firdaus Marbun (LPPM Universitas PGRI Sumatera Barat, 2020)
Impact of climate change for traditional fisherman is very real, especially in term of availability of production resources. Some of climate changes such as weather change, flooding, and lack of haul are resulting in vulnerability for traditional fisherman. Fisherman will always have ways to face every those changes. This matter is to ensure their existence in life. Sutera sub-district in Pesisir Selatan Regency where some its society work as traditional fisherman. As a coastal area, it can be sure that they are also faced for climate change. Using qualitative descriptive method, this research in purpose to see some changes which happened in Sutera Sub-districts as effect of climate change.Others, what strategies that they have done to overcome thase changes. The results of this study indicate that some of the Sutera District fishermen still rely on 'pesakitan' even though they are no longer relevant. The majority of fishermen use mass media as a source of information about weather forecasts and climate change. By sharing information in a stall, this information can be known. Next they make other alternatives such as catching shrimp and crabs when the weather is bad or a storm comes. Generally they avoid natural events as much as possible and expand the area of capture if the catch is minimal